Risk factors for crash involvement in older motorcycle riders. (February 2018) - Chen, Sy-Jou; Chen, Chih-Yi; Lin, Mau-Roung
Highlights: First study to identify risk factors for crash involvement in older motorcyclists. Impaired hearing & balance, speed, and crash experience increased risk of crashes. Obese older riders had a lower crash risk than those with a normal weight. Abstract: A prospective cohort study was conducted to identify risk and protective factors for crash involvement in older motorcyclists. Over a 1-year study period from August 2013 to July 2014, study participants were recruited from local community centers of five cities in Taiwan. People aged ≥60 years who rode a motorcycle at least once per week were eligible and were invited to participate in the study. Among 256 older riders who completed the baseline assessment and at least one of the four follow-up assessments, 79 (33.7%) experienced a motorcycle crash over the study period. Results of the proportional hazards model showed that after controlling for age, gender, and riding distance, older riders who had sustained hearing impairment (hazard ratio (HR) = 2.58; 95% confidence interval (CI), 1.30–5.15), rode a motorcycle at speeds of ≥41 km/h (HR = 2.31; 95% CI, 1.26–4.23), and had experienced a motorcycle crash in the past year (HR = 1.81; 95% CI, 1.06–3.09) were more likely to be involved in a crash, compared to their counterparts. Conversely, older riders who were obese (HR = 0.43; 95% CI, 0.22–0.82) were less likely to be involved in a crash than those with a normal weight, while longer functional reach distances (HR = 0.96; 95% CI, 0.93–0.99) and higher Tinetti balance scores (HR = 0.79; 95% CI, 0.69–0.91) were associated with a reduced risk of crash involvement. Among older people riding a motorcycle as their primary source of transportation, several factors associated with the occurrence of motorcycle crashes were identified. Restrictions and modifications of these risk factors may help design effective safety interventions for reducing crash and injury risks of this increasing riding population.